Meteorological Observations at Syowa Station in 1994 by the 35th Japanese Antarctic Research Expedition - Yuzuru Inagawa; Yoshikatsu Yamamoto; Yuji Taguchi; Toshihiro Abo; Osamu Ijima (National Institute of Polar Research, 1997)
This paper describes the results of meteorological observations carried out by the Meteorological Observation Team of the 35th Japanese Antarctic Research Expedition (JARE-35) from 1 February 1994 to 31 January 1995 at Syowa Station. The method of observations, instruments, and statistics at Syowa Station were the same as those of the JARE-34 observation team. The principal characteristics in the period of JARE-35 are as follows. 1) Blizzards at Syowa Station were encountered twenty-eight times spanning sixty days both of which are normal. 2) The Antarctic ozone hole was observed for six successive years. The lowest value of daily representative total ozone was 134m atm-cm on 27 September. Which was the lowest value in the historical record of Syowa Station.